Determining cut-off scores for simulated tasks in Brazilian Air Force military personnel - Botta, Willian Carrero; Magraner, J. M.; Orr, R. M.; Padovani, C. R. [UNESP]; Borin, J. P. (BMJ, 2024)
Introduction: Combat readiness assessments through simulated tasks (STs) have been developed for the Brazilian Air Force (BAF) to establish physical employment standards. Previous research has established BAF critical combat tasks with STs developed based on the physical demands of these tasks. Before implementing these STs, the standards required of BAF personnel must be established. The aim of this study was to determine the cut-off scores for five previously established STs. Methods: Eighty-eight cadets attended three different testing batteries in order to complete the five STs, being: Battery 1 (foot march), Battery 2 (plane crash on water and water survival skills) and Battery 3 (plane crash on land, obstacle course) with their times recorded. Cut-off scores were set at the 85th percentile of the data distribution with these values and then analysed by four subject matter experts (SMEs) using subjective criteria through criterion analysis. Results: All 88 cadets were submitted to the five assessments. After analysing the performance results on the STs, the SMEs discussed and agreed on the following cut-off scores: obstacle course (3:21 min:s), foot march (31:00 min:s), plane crash on land (1:25 min:s), plane crash on water (1:12 min:s) and water survival skills (4:03 min:s). Conclusion: The outcomes of this research allow for the five STs to be implemented in BAF cadets and qualified BAF personnel with the established cut-off scores used to monitor the operational capability of these personnel (be it for cadet training outcomes or unit preparedness assessments) and to guide conditioning practices if personnel are below standards.
Keywords: EDUCATION & TRAINING (see Medical Education & Training); OCCUPATIONAL & INDUSTRIAL MEDICINE; SPORTS MEDICINE